A Pedagogia Histórico- Crítica durante o governo de Roberto Requião (1991-1994) - Goncalves, Kassia Camila (2019)
This work had as objective to investigate the Historical-Critical Pedagogy (PHC) during the first government of the governor Roberto Requião, in the Paraná State, with emphasis in the years 1991-1994. The PHC had its implementation through the Basic Curriculum of the Public Schools of the State created in 1990. At first, to give a theoretical basis the research was necessary to approach the process of implementation of the PHC during the years of 1990 in the schools. In this context, in the first chapter, we approach the theme, education and PHC in the Paraná State. To understand what was happening in education in that period, and the historically approach of the PHC trajectory in the State. In the second chapter, we evaluated the main documents that directed education in the early 1990s. In order to understand the articulations and educational intentions in the administration of Requião. In the third chapter, we approached a document considered relevant to the education of this period entitled, Paraná: Building a Citizen School. With the objective of analyzing its fundamentals and principles, in addition to making a comparison between PHC and the Citizen School. And also, to identify possible theoretical divergences between the two pedagogical conceptions. As results, we show that PHC was not mentioned in the documents analyzed. On the contrary, there was a neoliberal discourse that aimed to train students for the new demands of the job market, in disarticulation with the foundations of CBEP centered on Historical-Critical Pedagogy.